Chemistry education students' perception toward their learning outcomes during online learning - Noviza Rizkia; Saura Alaifa Nazmi; Lisa Fitri Fiana; Muhammad Reza (Universitas Negeri Malang, 2023)
This study aims to determine the self-perception of chemistry education students related to online learning in the UIN Ar-Raniry. This descriptive research involved chemistry education students of the 2019 batch. Their perception was obtained using an online questionnaire with 15 questions. It can be concluded that implementing the online learning system does not entirely affect students' learning outcomes.   REFERENCES Al-Idrus, S. W., Muti'ah, M., & Rahmawati, R. (2021). Analisis Proses Pembelajaran Daring Selama Pandemi Covid-19 pada Mahasiswa Program Studi Pendidikan Kimia FKIP UNRAM. PENSA, 3(1 SE-Articles). https://ejournal.stitpn.ac.id/index.php/pensa/article/view/1246 Arisandi, Y., Dasna, I. W., Sumari, S., Habiddin, H., Ibnu, S., & Subandi. (2021). Promoting vocational students' perception and achievement towards Chemistry: SPARE Learning Strategy for students majoring in Automotive Engineering. Turkish Journal of Computer and Mathematics Education (TURCOMAT), 12(13), 6357-6365. Belawati, T. (2019). Pembelajaran Online. Universitas Terbuka. Habiddin, H., Yahmin, Y., Retnosari, R., Muarifin, M., Aziz, A. N., Husniah, I., & Anwar, L. (2020). Chemistry students' attitude towards chemistry. AIP Conference Proceedings, 2215(1), 20005. https://doi.org/10.1063/5.0000496 Mandailina, V., Pramita, D., & Haifaturrahmah, H. (2021). Pembelajaran Daring Dalam Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Selama Pandemi Covid-19: Sebuah Meta-Analisis. Indonesian Journal of Educational Science (IJES), 3(2), 120-129. Pratiwi, N. N., & Puspasari, D. (2021). PENGARUH PENGGUNAAN PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA. JAMP : Jurnal Administrasi Dan Manajemen Pendidikan; Vol 4, No 4 (2021): Volume 4 No 4 Desember 2021. https://doi.org/10.17977/um027v4i42021p320 Purwanto, A., Pramono, R., Asbari, M., Hyun, C. C., Wijayanti, L. M., Putri, R. S., & Santoso,  priyono B. (2020). Studi Eksploratif Dampak Pandemi COVID-19 Terhadap Proses Pembelajaran Online di Sekolah Dasar. EduPsyCouns: Journal of Education, Psychology and Counseling, 2(1), 1-12. Putri, M., & Kurniawati, Y. (2021). Students' learning interest using computer and android in acid base teaching. J-PEK (Jurnal Pembelajaran Kimia), 6(2), 63-71. http://dx.doi.org/10.17977/um026v6i22021p063 Putria, H., Maula, L. H., & Uswatun, D. A. (2020). Analisis Proses Pembelajaran dalam Jaringan (DARING) Masa Pandemi Covid- 19 Pada Guru Sekolah Dasar. Jurnal Basicedu, 4(4), 861-872. Riyana, C. (2019). Produksi Bahan Pembelajaran Berbasis Online. Universitas Terbuka. Wardani, S., Haryani, S., Harmiasri, R., & Sari, N. N. (2022). Implementation of Online Learning to Prepare the Youth Generation in the Disruptive Era. J-PEK (Jurnal Pembelajaran Kimia), 7(1), 9-21. https://doi.org/http://dx.doi.org/10.17977/um026v7i12022p009